Acute and long-term effects of sucralose on the water flea Daphnia magna on mobility, survival and reproduction at different temperature regimes. Issue 10 (25th November 2016) - Sladkova, S. V.; Kholodkevich, S. V.; Olsen, G. H.; Geraudie, P.; Camus, L.
ABSTRACT: Sucralose is a food additive used as a substitute for sugar. Although the risk of negative effects in organisms exposed to sucralose in the natural environment is low, it is expected that the water concentrations of sucralose will continue to increase in the near future. Temperature in the aquatic ecosystem is also expected to increase, and this needs to be considered in ecotoxicological studies. Herein, we investigated if the water flea Daphnia magna could be affected by sucralose exposure both at optimal and elevated temperatures. No increased mortality or effects on mobility and fecundity were observed after sucralose exposure at any exposure temperature during the course of the experiment. An increase in temperature to 26°С reduced the time required to produce four generations of offspring. However, this result was observed across treatments; hence speeding up of life processes was caused by an increased temperature only and not sucralose exposure. A lack of deleterious effects on the acute and chronic endpoints, even at elevated temperatures, suggests a relative robustness of this species to sucralose. However, due to the extensive use of sucralose in combination with rising water temperatures, further investigations on possible long-term effects should be studied to evaluate potential early warning signals.